Characterisation and phononic image reconstruction of gold nanorods - Naznin, Shakila (2023)
The optical and mechanical properties of metal nanoparticles depend mostly on their sizes and shapes. However, a non-destructive size characterisation technique for metal nanoparticles which can work in any external environment with high precision is currently unavailable. It is well known that optical microscopy is diffraction limited which means that two close objects are not resolvable because of the bending of light waves while passing through small apertures. The resolution of an optical system is limited to a few hundred nanometres for visible wavelengths, even using the highest available numerical aperture (1.4). This PhD research focused on both these problems: the unavailability of a precise and non-destructive size characterisation technique for metal nanoparticles applicable for all environments and the resolution limit of optical microscopy.